2002
DOI: 10.1038/sj.bjc.6600517
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of antibody directed enzyme prodrug therapy (ADEPT) in patients with advanced colorectal carcinoma or other CEA producing tumours

Abstract: Antibody-directed enzyme prodrug therapy is a targeted therapy in which a prodrug is activated selectively at the tumour site by an enzyme, which has been targeted to the tumour by an antibody (antibody-enzyme conjugate). Previous clinical trials have shown evidence of tumour response, however, the activated drug had a long half-life, which resulted in dose-limiting myelosuppression. Also, the targeting system, although giving high tumour to blood ratios of antibody-enzyme conjugate (10 000 : 1) required admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 18 publications
0
103
0
Order By: Relevance
“…Results from these experiments showed that only 23% of patients (three out of 13) treated with MFECPHis had detectable HACA after a single administration of MFECPHis (Figure 7), while 97% (36/37) of patients had detectable HACA when treated with A5CP in previous trials (Napier et al, 2000;Francis et al, 2002). Fisher's exact test confirmed statistical significance (Po0.0001) between the HACA response of these two patient groups.…”
Section: Human Polyclonal Antibody Response To Cpmentioning
confidence: 83%
See 4 more Smart Citations
“…Results from these experiments showed that only 23% of patients (three out of 13) treated with MFECPHis had detectable HACA after a single administration of MFECPHis (Figure 7), while 97% (36/37) of patients had detectable HACA when treated with A5CP in previous trials (Napier et al, 2000;Francis et al, 2002). Fisher's exact test confirmed statistical significance (Po0.0001) between the HACA response of these two patient groups.…”
Section: Human Polyclonal Antibody Response To Cpmentioning
confidence: 83%
“…and MFEdmCPHis (endotoxin 1.1 EU ml À1 ) and the second experiment comparing MFECPHis and A5CP (endotoxin o0.1 EU ml À1 ). A5CP was supplied by Lonza Biologics (UK) for the previous clinical trial (Francis et al, 2002) and consists of an F(ab 0 ) 2 derived from the affinity-purified monoclonal anti-CEA antibody A5B7 covalently linked to CP (Melton et al, 1993). Groups of eight Balb/c mice were injected 4 Â intraperitoneally (i.p.)…”
Section: Murine Immunisation Studiesmentioning
confidence: 99%
See 3 more Smart Citations